Herbal HuoXueTongFu Formula with anti-inflammatory and fibrinolytic activity regulation for the prevention of postoperative peritoneal adhesions - Lili Yang; Lili Yang; Yali Wang; Yali Wang; Zhengjun Li; Zhengjun Li; Wen Li; Yanqi Chen; Ziyang Kong; Huixiang Zhang; Jiafei Wu; Mingqi Shang; et al. (Frontiers in Immunology)
BackgroundThe HuoXueTongFu Formula (HXTF) originates from the classic prescription “DaHuangMuDan Decoction” from the “Synopsis of the golden chamber”. Our previous study revealed that HXTF has a positive effect on postoperative peritoneal adhesion (PPA). However, the specific mechanism of HXTF on PPA formation within the time-to-treatment window has not been fully elucidated. This study aimed to determine the critical roles of HXTF as a result of its specific anti-inflammatory and antifibrinolytic activities for PPA treatment.MethodsThe eight main bioactive components of HXTF were subjected to high-performance liquid chromatography-mass spectrometry. The core targets, critical biological processes, and underlying pathways of HXTF and PPA were identified via a series of network pharmacological methods. The specific anti-inflammatory function in the initial step of PPA formation was validated in peritoneal macrophages (PMs) isolated from PPA mice on Day 3 postsurgery. The potential anti-fibrinolytic activity in the next stage of PPA formation was subsequently explored in PPA mice on Day 7 postsurgery.ResultsNetwork pharmacology revealed 160 common targets between HXTF and PPA. Several core targets, i.e., matrix metalloproteinase 9 (MMP9), tissue-type plasminogen activator (tPA), and plasminogen activator inhibitor 1 (PAI-1), were annotated as important biological processes (extracellular matrix disassembly and the collagen catabolic process). Validation experiments revealed that HXTF could induce macrophage polarization-mediated anti-inflammatory reactions by increasing the phagocytic capacity of PMs and promoting the release of anti-inflammatory cytokines (IL-4 and IL-10). In addition, HXTF promoted fibrinogenolysis and improved fibrinolytic activity, thereby inhibiting collagen deposition and reducing adhesion development.ConclusionThe ameliorative effects of herbal HXTF on PPA formation are attributable to the induction of macrophage polarization-mediated anti-inflammatory reactions in the early stage of PPA formation and the promotion of fibrinogenolysis and fibrinolytic activity in the middle stage of PPA formation. HXTF may be a promising alternative agent for the prevention and treatment of PPA.